The Effect of Investment Decisions and Dividend Policy on Firm Value: The Mediating Role of Profitability in LQ45 Companies During the 2023–2025 Period - I Gede Abdi Pustaka; I Made Dauh Wijana; Gregorius Paulus Tahu (Digital Innovation : International Journal of Management, 2026)
The performance of the Indonesian capital market during the 2023–2025 period experienced significant challenges and dynamic fluctuations. These conditions affected the performance of listed companies, including those included in the LQ45 Index. In this study, company performance is represented by firm value, which may be influenced by several factors, including investment decisions, dividend policy, and profitability. This study aims to examine the effect of investment decisions and dividend policy on the firm value of LQ45 companies during the 2023–2025 period, with profitability serving as a mediating variable. Firm value represents the primary objective of companies in conducting business activities and is influenced by various internal factors, including investment decisions, dividend policy, and profitability. The population of this study consisted of LQ45 companies listed on the Indonesia Stock Exchange (IDX) during the 2023–2025 period. The sample comprised 27 companies that were consistently included in the LQ45 Index and distributed dividends to shareholders for three consecutive years. Data were analyzed using Structural Equation Modeling (SEM) based on the SmartPLS software. The findings reveal that investment decisions and profitability have a significant negative effect on firm value. In contrast, dividend policy has a significant positive effect on firm value. Furthermore, investment decisions and dividend policy exert a significant positive influence on profitability. Regarding the mediating role of profitability, the results indicate that profitability does not mediate the relationship between investment decisions and firm value, nor does it mediate the relationship between dividend policy and firm value.